The Mission of God : Studies in Orthodox and Evangelical Mission. - Oxbrow, Mark (Regnum studies in mission., 2015)
This is a 'must read' collection of essays that are rooted in prayer, in the Scriptures and in the rich histories of two very different traditions. The variety of topics and perspectives are presented by senior scholars and leaders, giving the reader an excellent glimpse into the ways in which Orthodox and Evangelical Christians around the globe have come together to participate in God's transforming mission. I highly recommend it for all pastors, seminary and Bible college students and staff.